Uma contribuição à análise de medidas de construtibilidade em obras de edificações prediais residenciais em alvenaria estrutural - Patricia Elizabeth Ferreira Gomes Barbosa (2013)
The present work aims contributing to the constructability study in buildings that use structural masonry as constructive system in mid-sized building construction companies. The work focuses the analysis, through prospective case study of constructability problems that are caused by design process failures and shortcomings. Problems identification made possible to point out an adaptation of constructability guidelines presented in international literature, to be used in the context of the projects. The case study was developed in mid-sized company. The design process of the company was characterized, work routines that impact on constructability were identified and constructability issues have been identified in two different sites. As a result, changes in the design process are outlined, and work routines are suggested. It was found that the main problems associated with constructability are caused by failures in the definition of the scope of the design disciplines, lack of communication between the designers and the coordination, particularly with regard to structural projects, and the failure in consideration of production projects in feasibility analysis and design. Possible measures to constructability improvement are briefly outlined.